Intravenous ibandronate injections given every three months: a new treatment option to prevent bone loss in postmenopausal women. Issue 10 (12th September 2003) - Stakkestad, J A; Benevolenskaya, L I; Stepan, J J; Skag, A; Nordby, A; Oefjord, E; Burdeska, A; Jonkanski, I; Mahoney, P
Abstract : Objective: To investigate the efficacy, safety, and dose response of three doses of ibandronate, given intermittently by intravenous (IV) injection every three months, in preventing postmenopausal osteoporosis. Patients and methods: 629 postmenopausal women, categorised according to time since menopause and baseline lumbar spine (L1–4) bone mineral density (BMD), were enrolled into a multicentre, double blind, placebo controlled trial. They were randomly allocated to receive IV ibandronate 0.5 mg, 1 mg or 2 mg, or placebo every three months. All women received daily calcium supplementation. Results: One year's treatment with intermittent IV ibandronate injections produced a dose dependent gain in mean (SD) lumbar spine BMD from baseline of 2.5 (2.5)%, 1.8 (2.6)%, and 1.0 (2.8)% in the groups receiving 2 mg, 1 mg, and 0.5 mg ibandronate, respectively, compared with a loss of BMD of 0.4 (2.4)% in the women in the placebo group; p=0.0001 for each ibandronate dose v placebo. Highest BMD gains occurred in women with osteopenia receiving 2 mg ibandronate. Similarly, at the hip, all three doses of ibandronate produced significantly better gains in BMD than placebo (p<0.05), with the greatest gains in the women with osteopenia receiving the 2 mg dose. Ibandronate concomitantly and dose dependently suppressed markers of bone turnover in comparison with placebo, and injections were well tolerated. Conclusion: IV ibandronate injections, given every three months, may be an effective alternative to oral bisphosphonates and hormonal therapy in the prevention of bone loss in postmenopausal women.